Estrogen effects on the brain: actions beyond the hypothalamus via novel mechanisms - McEwen, Bruce S. (2012)
From its origins in how the brain controls the endocrine system via the hypothalamus and pituitary gland, neuroendocrinology has evolved into a science that now includes hormone action on many aspects of brain function. These actions involve the whole central nervous system and not just the hypothalamus. Advances in our understanding of cellular and molecular actions of steroid hormones have gone beyond the important cell nuclear actions of steroid hormone receptors to include signaling pathways that intersect with other mediators such as neurotransmitters and neuromodulators. This has, in turn, broadened the search for and identification of steroid receptors to include non-nuclear sites in synapses, dendrites, mitochondria and glial cells, as well as cell nuclei. The study of estrogen receptors and estrogen actions on processes related to cognition, mood, autonomic regulation, pain and neuroprotection, among other functions, has led the way in this new view of hormone actions on the brain. In this review we summarize past and current work in our laboratory on this topic. This exciting and growing field involving many laboratories continues to reshape our ideas and approaches to neuroendocrinology both at the bench and the bedside.